Implementation of School-Based Management (Case Study at SMP Negeri 3 Pule-Trenggalek) - Susanto, Edi (Jurnal Aplikasi Manajemen, 2014)
The aims of this study are to: (1) know the basic concept of school-based management and all its components, (2) know how far the extent to which implications of Education Management in Education Quality Improvement, (3) know the implementation of schoolbased management in SMP Negeri 3 Pule Trenggalek in the year 2014/2015, (4) know the school-based management strategies in SMP Negeri 3 Pule Trenggalek in the year 2014/2015, (5) know the factors in which support the success of school-based management. The results of a school-based management review are: (1) The existence of the authority towards the school to carry out the management and continuously improve the quality by involving all members of groups who are associated directly with the school in the decision-making process in order to fulfill the school needs of quality improvement. (2) The implications of the presence of school-based management is to provide chances and opportunities for principals, teachers and students for educational innovation. (3) The school-based management implementation at SMP Negeri 3 Pule is based on the visions, missions and goals set. (4) The strategy that is implemented by the school include (a) a self-evaluation to analyze the strengths and weaknesses of the school. (b) set the quality of indicators or targets to be achieved. (c) monitoring and evaluating the programs that have been planned in accordance with the funding to see the achievement of the visions, missions and goals. (5) The supporting factors of the success of school-based management are covering: (a) Leadership and management of good schools, (b) social conditions, economic and public appreciation of education, (c) the government support, and (d) professionalism.